Analisis Yuridis Proses Penyelesaian Tindak Pidana Terhadap Pelaku Penipuan Melalui Pembayaran Elektronik Untuk Mewujudkan Perlindungan Hukum - Muhammad Noval; Ramon Nofrial; Siti Nurkhotijah (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2022)
Article 45A paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 states that any person who intentionally and without rights spreads false and misleading news that results in consumer losses in Electronic Transactions shall be punished with imprisonment and/or or fines. The fraud that occurred at One Mall Batam carried out through fake or fictitious electronic transactions cost the victim a total of 30 million rupiah. Purpose: The purpose of this study is to determine the regulation of criminal law against perpetrators of fraud through electronic payments in order to realize legal protection. And to find out the implementation, constraint factors and solutions in preventing and overcoming the rise of fraud in electronic payments. This research method is empirical juridical. Methodology: This research consists of literature study and is also supported by field studies through interviews with respondents. Results: The results of the study indicate that the regulation of criminal law against criminals through electronic payments in realizing legal protection, namely Article 378 of the Criminal Code which regulates special crimes, is also specifically regulated in Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which regulates criminal acts of fraud committed through electronic transactions and is subject to a maximum criminal penalty of 6 (six) years and/or a maximum fine of Rp. 1,000,000,000 ,00 (one billion rupiah). Implementation in preventing and overcoming the rise of fraud in electronic payments is carried out by optimally criminalizing the perpetrators of crimes committed through electronic transactions. Limitations: The constraint factor faced is that there are many types of electronic transactions that cannot be reported directly, making it easier to ensure the results of daily reports. Contribution: The solution is that the victim must be more careful in accepting every payment through an electronic transaction, the victim must have the equipment to verify the proof of the electronic payment. It is recommended for law enforcement officers to optimize the performance of law enforcement for electronic transactions and dismantle tricks or methods applied by perpetrators to prevent other victims, victims to be more careful and thorough in accepting electronic transactions and must ensure first in advance of any payments made.